Revealing the Potential of Fucus vesiculosus Linnaeus for Cosmetic Purposes: Chemical Profile and Biological Activities of Commercial and Wild Samples - Marina Muñoz-Quintana; Carolina Padrón-Sanz; Marina Dolbeth; Francisco Arenas; Vitor Vasconcelos; Graciliana Lopes (Marine Drugs)
The natural products industry is gaining increasing interest, not only due to modern lifestyles becoming more aware of environmental and sustainability issues but also because of the loss of efficacy and undesirable side effects of synthetic ingredients. This pioneering study provides a comprehensive comparison between extracts obtained from wild and commercial samples of Fucus vesiculosus Linnaeus, highlighting their multifaceted benefits in cosmetic applications. The antiaging potential of acetone (70 and 90%) and ethanol 60% extracts from wild and commercial samples of F. vesiculosus, focusing on their application in cosmetics, was explored. The extracts were chemically characterized, their carotenoid profiles being established by HPLC, and the total phenolic content and phlorotannins by spectrophotometry. The extracts were evaluated for their antioxidant potential against the physiologic free radicals superoxide anion radical (O2•−) and nitric oxide (•NO), for their ability to inhibit the enzymes hyaluronidase and tyrosinase, and for their anti-inflammatory potential in the macrophage cell model RAW 264.7. The acetone 70% extract of wild F. vesiculosus was the richest in fucoxanthin, which accounted for more than 67% of the total pigments identified, followed by the acetone 90% extract of the same sample, where both fucoxanthin and pheophytin-a represented 40% of the total pigments. The same behavior was observed for phenolic compounds, with the ethanol 60% presenting the lowest values. A chemical correlation could be established between the chemical composition and the biological activities, with acetone extracts from the wild F. vesiculosus, richer in fucoxanthin and phlorotannins, standing out as natural ingredients with anti-aging potential. Acetone 90% can be highlighted as the most effective extraction solvent, their extracts presenting the highest radicals scavenging capacity, ability to inhibit tyrosinase to a greater extent than the commercial ingredient kojic acid, and potential to slow down the inflammatory process.